PENGARUH SUBSTITUSI TEPUNG KEDELAI TERHADAP KUALITAS BISKUIT - Susilowati, Heni; Prabowo, Adi (Sekolah Tinggi Pariwisata AMPTA, 2018)
The research entitled The Effect of Substitution of Soybean Flour on Biscuit Quality is a type of research using quantitative approach with experimental method. The purpose to know the effect of quality biscuit with soybean flour substitution with different percentage that is equal to 50%, 25% and 10% viewed from aspect of color, flavor, aroma and texture. The experiments used 3 different types of treatment on the percentage of soy flour used ie, biscuit A with 50% soy flour, biscuit B with 25% soy flour, and C biscuits with 10% soy flour.Methods of data collection using subjective assessment of sensory tests taken from the results of a panelist assessment that includes assessment of color, aroma, taste and texture on biscuits. The panel of researchers was 30 people taken by random sampling technique with considerations that included panelist knowledge about the sensory properties of biscuits in general. Methods of data analysis to test the hypothesis using the analysis of single classification variables and tukey test, previously conducted prasarat test that is homogeneity test and normality test. The result of the research with Anova test seen from the color aspect shows that (significant value (p-value)